Comparison of three modalities of plasmapheresis on coagulation: Centrifugal, single‐membrane filtration, and double‐filtration plasmapheresis. Issue 3 (28th January 2021) - Marlu, Raphaël; Naciri Bennani, Hamza; Seyve, Landry; Noble, Johan; Chevallier, Eloi; Motte, Lionel; Imerzoukene, Farida; Bugnazet, Mathilde; Christophe, Maryvonne; Malvezzi, Paolo; Jouve, Thomas; Rostaing, Lionel
Abstract: Background: Plasmapheresis can deplete pathogenic antibodies and allow ABO‐ and/or HLA‐incompatible transplantation. Aim: To determine the impacts of three modalities of plasmapheresis (centrifugal plasmapheresis [cTPE], single‐filtration plasmapheresis [mTPE], double‐filtration plasmapheresis [DFPP]) on hemostasis parameters and thrombin generation. Materials/Methods: Prospective, comparative study on 21 patients that received three modalities of plasmapheresis (7 patients/group). Hemostasis (prothrombin time [PT], activated partial thromboplastin time [aPTT], procoagulant factors and natural anticoagulants) were measured before and after the first plasmapheresis session. Thrombin generation was also assessed in platelet‐poor plasma using an STA‐Genesia (Stago) analyzer and Thromboscreen reagents (Stago) in 4‐5 patients from each group. Results: Both cTPE and mTPE resulted in high decreases in proteins, whatever their molecular weights. Median post/pre ratios were 0.27 to 0.55 for cTPE for most proteins (except FVIII [0.64] and VWF [0.57]). Median post/pre‐ratios of mTPE were 0.28 to 0.56 for all proteins. DFPP decreased high‐molecular‐weight proteins (fibrinogen, FV, FVIII, FXI, VWF) and proteins strongly bound to large molecules (protein SandTFPI). Median post/pre ratios with cTPE and mTPE were similar to DFPP for fibrinogen and FXIII. Regarding thrombin generation, cTPE and mTPE did not significantly modify endogenous thrombin potential (ETP) and DFPP induced a slight decrease in ETP (median post/pre ratio at 0.73) in the absence of thrombomodulin. ETP inhibition by thrombomodulin was decreased for all procedures. Conclusions: DFPP depleted high molecular‐weight proteins in contrast to cTPE and mTPE, which significantly decreased all proteins. Regarding thrombin generation, depletion of procoagulant factors was counterbalanced by a decrease in some natural anticoagulants whatever plasmapheresis method used; with all methods, fibrinogen and FXIII were highly depleted.